Medical malpractice and sarcoma care—A thirty‐three year review of case resolutions, inciting factors, and at risk physician specialties surrounding a rare diagnosis. Issue 8 (22nd August 2014) - Mesko, Nathan W.; Mesko, Jennifer L.; Gaffney, Lauren M.; Halpern, Jennifer L.; Schwartz, Herbert S.; Holt, Ginger E.
<x xml:space="preserve">Abstract</x> Background We reviewed medico‐legal cases related to extremity sarcoma malpractice in order to recognize those factors most commonly instigating sarcoma litigation. Methods Over one million legal cases available in a national legal database were searched for malpractice verdicts and settlements involving extremity sarcoma spanning 1980–2012. We categorized verdict/settlement resolutions by state, year, award amount, nature of the complaint/injury, specialty of the physician defendant, and academic affiliation of defendant–amongst other variables. Results Of the 216 cases identified, 57% of case resolutions favored the plaintiff, with a mean indemnity payment of $2.30 million (range $65, 076–$12.66 million). Delay in diagnosis (81%), unnecessary amputation (11%), and misdiagnosis (7%) accounted for the majority of complaints. The greatest numbers of claims were filed against primary care specialties (34%), orthopaedic surgeons (23%), and radiologists (12%). Individual state tort reform measures were not protective against case resolution outcome. Conclusions Reported medico‐legal claims involving sarcoma care continue to rise, with mean indemnity payments approaching 10 times that for other reported medical/surgical specialties. Primary care and orthopaedic specialties are the most commonly named physician defendants, citing a delay in diagnosis. This suggests further education in the front line diagnosis and management of sarcomas is needed. J. Surg. Oncol. 2014; 110:919–929. © 2014 Wiley Periodicals, Inc.